Chilean Growth through East Asian Eyes - Kharas, Homi; Leipziger, Danny; Maloney, William; Thillainathan, R.; Hesse, Heiko (World Bank, Washington, DC, 2017)
Chile could well have space to increase its growth potential by 2 percentage points of Gross Domestic Product (GDP) per year. To do this, it would need to pay more attention to new sources of growth in natural resources, manufacturing, and services. In an increasingly globalized world, first-mover advantages have become more numerous and larger. Chile risks losing out, as a few recent high-profile cases suggest. Chile's total factor productivity growth can be raised by driving within-firm technological change closer to the global best-practice frontier more rapidly, especially in manufacturing. This would encourage the diversification of exports and boost Chile's supply response to global demand changes. Chile confronts obstacles in its processes of innovation, human capital accumulation, and investment. To overcome them, deep institutional changes are needed to develop a national innovation system, stronger and more equitable educational achievement, more flexible labor markets, and focused public investments that crowd in private business. Such an inclusive growth strategy is likely to yield better social outcomes than a strategy that attempts to confront social inequities head-on through more equitable access to public services without paying adequate attention to the demand for labor and generation of income. Chile could also try a new policy towards innovation, but it would need to be bolder in terms of the institutional design to maximize the chances of success.